2015
DOI: 10.5268/iw-5.1.738
|View full text |Cite
|
Sign up to set email alerts
|

Storm-triggered, increased supply of sediment-derived phosphorus to the epilimnion in a small freshwater lake

Abstract: This study investigated internal loading of sediment-derived phosphorus (P) in a small, meso-eutrophic lake (surface area 0.2 km 2 , catchment area 2.7 km 2 , mean depth 6 m, maximum depth 14 m) on the Atlantic seaboard of western Europe. High resolution data collected over 2.5 years (1 Mar 2011 to 30 Sep 2013) revealed inconsistent patterns in (1) the timing and magnitude of lake turnover and (2) the relative importance of the transfer of hypolimnetic sediment-derived P to the epilimnion when compared with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…The potential of phytoplankton growth being boosted by storm-induced nutrient upwelling in lakes has been reported by observational studies (e.g. Soranno et al 1997;MacIntyre and Jellison 2001;Crockford et al 2015;Giling et al 2017). Increases in phytoplankton after storms in the first numerical experiment were also seen when incoming shortwave radiation was high.…”
Section: Causal Factors Regulating Phytoplankton Response To Stormssupporting
confidence: 55%
“…The potential of phytoplankton growth being boosted by storm-induced nutrient upwelling in lakes has been reported by observational studies (e.g. Soranno et al 1997;MacIntyre and Jellison 2001;Crockford et al 2015;Giling et al 2017). Increases in phytoplankton after storms in the first numerical experiment were also seen when incoming shortwave radiation was high.…”
Section: Causal Factors Regulating Phytoplankton Response To Stormssupporting
confidence: 55%
“…The strong vertical heterogeneity in nutrient levels induces the possibility that mixing events causing entrainment of hypolimnetic water into the epilimnion can lead to spikes of epilimnetic nutrient concentrations (Lehmann et al., 2015), stimulating phytoplankton blooms (Giling, Nejstgaard, et al., 2017). These events can be caused by extreme weather events such as storms, cold spells, or river floods (Crockford et al., 2015; Soranno et al., 1997). With increased stratification in summer, the amount of energy needed for these deep mixing events increases, but the nutrient pulse after such an event tends to be stronger (Coats et al., 2006).…”
Section: Physical Chemical and Biological Consequences Of Enhanced Stratificationmentioning
confidence: 99%
“…Warming can impact the strength and persistence of stratification and the extent, severity, and duration of hypoxia (Jenny et al, 2014;Kraemer et al, 2015). Warming-induced increases in storminess can cause a more frequent breakdown of stratification or prevent lake stratification entirely (Crockford, Jordan, Melland, & Taylor, 2015), while changes in precipitation can influence inputs and effects of pollutants, including phosphorus (P) and nitrogen (N). Past studies have demonstrated the importance of climate in regulating ecosystem structure, and it is clear that climate and nutrients can act together in driving changes in lake ecosystems (Leavitt et al, 2009;McGowan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%